Effects Of Ifrs 15 On Revenue Recognition in the Oil And Gas Sector (Experience of Jsc "Uzbekneftegaz") - Munisabonu Toshpulatova (Academia Open, 2026)
General Background: International Financial Reporting Standard 15 (IFRS 15) "Revenue from Contracts with Customers" transformed revenue recognition practices across industries by introducing a control-based model that replaced the traditional risk-and-reward approach. The oil and gas sector, characterized by complex contractual arrangements, variable pricing mechanisms, and diverse delivery methods, faces unique challenges in implementing this standard. Specific Background: JSC Uzbekneftegaz, as Uzbekistan's leading oil and gas enterprise, transitioned to IFRS 15 in 2018, requiring comprehensive adjustments to its revenue accounting methodology. Knowledge Gap: Limited empirical evidence exists regarding the practical implementation effects of IFRS 15 within Central Asian extractive industries, particularly concerning long-term contracts and variable consideration treatment. Aims: This study analyzes the impact of IFRS 15 adoption on revenue recognition practices at JSC Uzbekneftegaz by examining consolidated financial statements from 2018-2024 and interim 2025 data. Results: Implementation resulted in substantial methodological changes including indirect tax exclusion, enhanced variable consideration estimation, and time-based revenue recognition for specific services, though economic substance remained largely unchanged. Novelty: This research provides the first comprehensive empirical analysis of IFRS 15 application in Uzbekistan's oil and gas sector. Implications: Findings demonstrate that IFRS 15 enhances financial transparency, international comparability, and analytical utility of revenue data in extractive industries.Keywords : IFRS 15, Revenue Recognition, Oil and Gas Industry, Uzbekneftegaz, Financial Reporting StandardsHighlight : Excluding indirect taxes from revenue improved transparency and international comparability of financial statements. Control-based recognition model clarified timing for long-term contracts and service-related revenue allocation. Variable consideration estimation enhanced measurement prudence, reducing risk of overstated financial results.